Capital Structure and Firm Performance in the Nigerian Cement Industry - Gambo, EL-Maude Jibreel; Abdul-Rahman, Ahmad; Ahmad, Mohammed Musa (Archives of Business Research, 2016)
The study examines the impact of capital structure on financial performance of firms in Nigerian cement industry. The population of the study 7 companies, a sample of 4 listed companies were selected. The research design is ex-post factor using two models to analyse the impacts of long term and short term debts on Return on Assets (ROA) and Return on Equity (ROE). The study uses balanced panel data of 20 observations from the 4 listed companies for the periods ranging from 2010-2014. Descriptive statistics, correlation and regression are used as tools of analysis. The study reveals that, there is statistically significant effect between long and short term liability on Return on Assets (ROA) and Return on Equity (ROE). The study however, concluded that the performance of companies in the cement industry is not optimized as a result of their inability to utilized debts in their capital structures. Finally, the paper recommends that, cement companies should encourage the use of long term debt in there capital structure since it has positive impact on their financial performance.